Pengaruh Pelatihan Kecerdasan Emosional dan Motivasi Terhadap Perilaku Caring dengan Soft Skill Sebagai Mediasi - Lesnussa, Merya Meisce C.; Sugiarto, Agus (Universitas Proklamasi 45, 2024)
The development of globalization, the rapid development of technology, and increasing public awareness of the importance of health, have made society's demands increasingly complex, holistic, comprehensive, responsive, affordable, and quality for the health services provided. Nurses as human resources play an important role in providing health services in hospitals. Quality nursing services are realized through the provision of nursing care based on nurses' caring behavior because it can influence client satisfaction and is an indicator of the quality of nursing services. This research has a goal to examine the effect of emotional intelligence training and motivation on caring behavior with soft skills as a mediation variable. This research was carried out at X hospital in City Salatiga. This research is explanatory research with a quantitative approach. The distribution of questionnaires is made by distributing questionnaires online to respondents. In this study, the population was medical nursing employees at X hospital in City Salatiga. The number of samples obtained was 113 respondents who met the research criteria. The research results showed that emotional intelligence training did not affect on soft skills and caring behavior. On the other hand, motivation influences nurses' soft skills and caring behavior. Furthermore, soft skills do not mediate emotional intelligence training on caring behavior, but soft skills have a role in mediating motivation and caring behavior.